Evaluation of an indirect assessment for identifying tasks for functional analysis. - Wiggins, Holly C.; Roscoe, Eileen M. (Journal of Applied Behavior Analysis (John Wiley & Sons, Inc.), 2020)
Although a demand analysis is helpful for identifying potential establishing operations for the functional analysis (FA) demand condition, it may not always be practical due to time constraints. A potential alternative is the Negative Reinforcement Rating Scale (NRRS), an indirect assessment tool that may serve as a time efficient alternative to a demand analysis. The experimenter assessed the reliability and validity of the NRRS for 5 individuals with autism spectrum disorder who exhibited problem behavior. Multiple types of interrater reliability were assessed across 2 informants, and NRRS outcomes were compared to a subsequent demand analysis and FA to assess its validity. Reliability was high (M = 84%) for NRRS numerical ratings of categories but low (M = 32.9%) for specific examples provided. NRRS‐identified highly aversive tasks yielded better correspondence with demand analysis outcomes than did NRRS‐identified less aversive tasks.